2004
DOI: 10.1248/bpb.27.1014
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Iridoid Total Glycoside from Cornus officinalis on Prevention of Glomerular Overexpression of Transforming Growth Factor Beta 1 and Matrixes in an Experimental Diabetes Model

Abstract: Diabetic nephropathy (DN), a common complication in patients with either type I or type II diabetes mellitus, has long been recognized to cause severe morbidity and mortality. It is also a major cause of chronic renal failure involved in dialysis therapy.1,2) DN is structurally characterized with the early appearance of hypertrophy in glomerular and tubular components, the subsequent development of thickened glomerular and tubular basement membranes, and the progressive accumulation of extracellular matrix (EC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 30 publications
(18 reference statements)
1
32
0
Order By: Relevance
“…The total iridoid glycosides of Corni Fructus containing loganin and morroniside inhibit oxidative stress 7) and prevent the renal overdeposition of fibronectin and laminin in an experimental diabetic rat model. 8) In particular, morroniside, one of the most abundant iridoid glycosides in Corni Fructus, has been proven effective in preventing diabetic complications such as diabetic angiopathy and the early stages of diabetic nephropathy by regulating renal mesangial cell growth through inhibiting oxidative stress. 9,10) In addition, it exhibits a neuroprotective effect by providing cytoprotection against H 2 O 2 -toxicity in SH-SY5Y cells.…”
mentioning
confidence: 99%
“…The total iridoid glycosides of Corni Fructus containing loganin and morroniside inhibit oxidative stress 7) and prevent the renal overdeposition of fibronectin and laminin in an experimental diabetic rat model. 8) In particular, morroniside, one of the most abundant iridoid glycosides in Corni Fructus, has been proven effective in preventing diabetic complications such as diabetic angiopathy and the early stages of diabetic nephropathy by regulating renal mesangial cell growth through inhibiting oxidative stress. 9,10) In addition, it exhibits a neuroprotective effect by providing cytoprotection against H 2 O 2 -toxicity in SH-SY5Y cells.…”
mentioning
confidence: 99%
“…4,5) Several pharmacological actions such as anti-neoplasm, antiinflammation, hepatoprotection, and anti-diabetic nephropathy were elucidated from the crude extract of fruit of C. officinalis. 6,7) However, there is little information about the pharmacological action of cornuside. The present study, therefore, was designed to examine the effects of cornuside on the expression levels of cytokine-induced proinflammatory and adhesion molecules, which could account for its beneficial effect in the cardiovascular system.…”
mentioning
confidence: 99%
“…24,25) Furthermore, several reports of its use including traditional medicine have been made, e.g., Vareed et al 26) reported that Corni Fructus has been used for improving liver and kidney functions, and iridoid total glycoside has the effect of preventing the overexpression of transforming growth factor-b 1 and matrixes in glomeruli with a diabetic model. 27) Moreover, we have previously reported that not only Hachimi-jiogan, containing Corni Fructus, could prevent the development of type 1 and 2 diabetic nephropathy, 3,4) and also that Corni Fructus led to a better AGE clearance due to improving the renal function than aminoguanidine, the prototype AGE inhibitor, suggesting that Corni Fructus might become an effective remedy against diabetic AGE accumulation.…”
Section: Discussionmentioning
confidence: 99%